2003
DOI: 10.1073/pnas.2230238100
|View full text |Cite
|
Sign up to set email alerts
|

Id-1 as a molecular target in therapy for breast cancer cell invasion and metastasis

Abstract: Mammary epithelial cells constitutively expressing Id-1 protein are unable to differentiate, acquire the ability to proliferate, and invade the extracellular matrix. In addition, Id-1 is aberrantly over-expressed in aggressive and metastatic breast cancer cells, as well as in human breast tumor biopsies from infiltrating carcinomas, suggesting Id-1 might be an important regulator of breast cancer progression. We show that human metastatic breast cancer cells become significantly less invasive in vitro and less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
193
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(211 citation statements)
references
References 34 publications
14
193
1
1
Order By: Relevance
“…Mobilization of endothelial cell progenitors from the bone marrow is also severely perturbed in Id knockout mice consistent with this hypothesis (10,11). On the other hand, a role for Id1 in modulating tumor epithelial cell behavior is suggested by the fact that overexpression of Id1 in cell lines results in increased invasiveness and metastatic potential of these cells, whereas reduction of high levels of Id1 present endogenously in these lines leads to an inhibition of these properties (12)(13)(14)(15)(16)(17).…”
Section: Introductionsupporting
confidence: 55%
“…Mobilization of endothelial cell progenitors from the bone marrow is also severely perturbed in Id knockout mice consistent with this hypothesis (10,11). On the other hand, a role for Id1 in modulating tumor epithelial cell behavior is suggested by the fact that overexpression of Id1 in cell lines results in increased invasiveness and metastatic potential of these cells, whereas reduction of high levels of Id1 present endogenously in these lines leads to an inhibition of these properties (12)(13)(14)(15)(16)(17).…”
Section: Introductionsupporting
confidence: 55%
“…Moreover, we demonstrated that E6/E7 onco-proteins of HPV type 16 convert non-invasive breast cancer cells to an invasive phenotype (Yasmeen et al, 2007a); this is accompanied by an overexpression of Id-1, which regulates cell invasion and metastasis of human breast cancer cells (Desprez et al, 1998;Fong et al, 2003). In this study, we investigated the relation between high-risk HPVs and Id-1 expression in breast cancer tissues from Syrian women.…”
Section: Discussionmentioning
confidence: 96%
“…Id-1 has been shown to promote metastasis in several different types of cancer. Overexpression of Id-1 promotes mammary epithelial cell invasion (Desprez et al, 1998), and reduced expression of Id-1 in metastatic breast cancer cells leads to a decrease in invasiveness in vitro (Fong et al, 2003). Overexpression of Id-1 in prostate cancer cells also promotes metastasis through increased angiogenesis and invasiveness (Coppe et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a high-level expression of Id-1 has been shown to be associated with poor prognosis of early-stage cervical cancer (Schindl et al, 2001), node-negative breast cancer (Schoppmann et al, 2003) and malignant melanoma (Straume and Akslen, 2005). Id-1 has also been shown to promote metastasis through increasing invasiveness and angiogenesis in breast and prostate cancer (Fong et al, 2003;Ling et al, 2005). High level of Id-2 has been demonstrated to reduce breast cancer cells invasiveness and therefore could act as a favourable prognostic marker for breast cancer patients (Stighall et al, 2005).…”
mentioning
confidence: 99%